2020
DOI: 10.3390/cancers12051100
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments of Systemic Chemotherapy for Gastric Cancer

Abstract: Gastric cancer (GC) is a molecularly heterogeneous disease. Its molecular background, epidemiology, and standard of care are quite different between Eastern and Western countries. Many efforts have been made in developing more effective surgeries and adjuvant chemotherapies for resectable GC in each region. Recently, an intensive combination of cytotoxic agents has been established as a new standard of adjuvant treatment. Meanwhile, palliative chemotherapy is a uniform standard treatment for unresectable GC wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 140 publications
(176 reference statements)
0
30
0
Order By: Relevance
“…GC samples with survival data and gene expression pro les were obtained from the GSE62254 dataset as shown in Table 1. The sample characteristics of GSE62254 were consistent with randomized clinical studies of GC [3,14,15]. The prognostic value of PolG was evaluated by Kaplan-Meier analysis which showed that low expression of PolG was associated with worse overall survival (OS, log-rank P < 0.001) as well as progression-free survival (PFS, log-rank P < 0.001) (Fig.…”
Section: Prognostic Value Of Polg In Gcmentioning
confidence: 73%
See 1 more Smart Citation
“…GC samples with survival data and gene expression pro les were obtained from the GSE62254 dataset as shown in Table 1. The sample characteristics of GSE62254 were consistent with randomized clinical studies of GC [3,14,15]. The prognostic value of PolG was evaluated by Kaplan-Meier analysis which showed that low expression of PolG was associated with worse overall survival (OS, log-rank P < 0.001) as well as progression-free survival (PFS, log-rank P < 0.001) (Fig.…”
Section: Prognostic Value Of Polg In Gcmentioning
confidence: 73%
“…Major efforts have been made in GC treatment including targeted therapies such as HER2-targeted trastuzumab, VEGFR2-targeted ramucirumab, and immune checkpoint inhibitors (ICIs) [2]. In addition to these improvements, the complex biology of GC often results in treatment failure and therapeutic resistance [3]. Therefore, it is necessary to further explore novel treatment targets, and adopt comprehensive treatment approaches to deliver better patient outcomes in GC.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy as an indispensable adjuvant treatment strategy has been routinely applied to the advanced stage GC. To effectively suppress tumor growth and metastasis, some combination regimens can simultaneously restrain several oncogenic pathways which are recommended to use [ 93 ]. However, how to alleviate the chemotherapy resistance and toxicity has become an urgent issue in order to provide better treatment of GC patients.…”
Section: Applications Of Circrna In Gcmentioning
confidence: 99%
“…Furthermore, two randomized phase II trials are currently ongoing: the DANTE trial (NCT 03421288) evaluating peri-operative use of atezolizumab (anti-PD-L1 antibody) combined with FLOT (docetaxel, oxaliplatin, leucovorin and 5-fluorouracil) [ 160 ] and the IMAGINE NCT04062656 randomized, four-arm, chemotherapy-controlled modular trial in subjects with histologically confirmed, resectable GC or GEJ adenocarcinoma. An increase to 35% is estimated to be clinically relevant when patients are treated with either nivolumab in combination with chemotherapy or nivolumab and another immuno-oncology agent (e.g., ipilimumab or relatlimab) [ 161 , 162 ]. Great interest is now addressed to the combination of ICIs and targeted molecules, which seems to be promising although findings are still afar to be conclusive.…”
Section: Immunotherapies: Novel Insights and Advancesmentioning
confidence: 99%